The role of multidetector computed tomography and magnetic resonance recent imaging techniques in the evaluation of intra-conal orbital lesions - Hoda Abdel Kareem; Manal F. Abou Samra; Mohamed Farouk Osman (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Objective: The purpose of our study was to assess the role of multi-detector computed tomography and magnetic resonance recent imaging techniques in the evaluation of intra-conal orbital lesions. Subjects and methods: 30 patients presented to the Ophthalmic and Radiology Departments at El-Minia University Hospital and El Minia Oncology Center with clinical diagnosis of visual loss and proptosis. They presented during the period from June 2012 to October 2013. Their ages range from 5 to 73 years. All patients subjected to MDCT and MRI. Also, contrast injection was injected on some cases. 24 patients were subjected to surgery and histopathology to confirm the radiological diagnosis. Results: A total of 30 patients were included (their mean age 26 years). 8 lesions were diagnosed inflammatory in nature (4 were orbital abscess and 4 were idiopathic orbital inflammatory disease i.e. pseudo tumors). 10 lesions were diagnosed as vascular lesions (2 lesions were carotid cavernous fistula and 8 lesions were cavernous hemangiomas). 6 lesions were diagnosed as optic nerve gliomas and other 6 lesions were diagnosed optic nerve sheath meningiomas. Conclusion: The use of MDCT and MRI recent techniques are mandatory for accurate diagnosis of the nature of intra-conal orbital mass lesions.